METABOLIC ALTERATIONS ASSOCIATED TO PHYSICAL EXERCISE OF SWIMMING AND THE INCREASE OF THE SIMPLE CARBOHYDRATE IN THE DIET OF FEMALE RATS (Fiep Bulletin - online, 2015)
The experiment aimed to study the metabolic alterations in glycemia and in the lipidic profile associated to the increase in the simple carbohydrate in the diet of Wistar rats submitted the continuous physical exercise of swimming. The animals were divided in four groups: sedentary with and without the addition of sucrose diluted 5% in water in the diet and, trained with and without the addition of sucrose diluted 5% in water in the diet; where they had swum 1 hour per day, 5 days per week during 8 weeks, with 5% overweight. A bigger total cholesterol concentration was found in the sedentary animals with relation to the trained ones and in the animals with diet with the addition of sucrose in relation to those that had not received sucrose in the diet. A significant difference between the groups sedentary and trained was observed when we compared groups with or without the addition of sucrose with the diet, in regard to concentration of triglycerides. The trained animals had presented bigger levels of HDL when compared with the sedentary ones. We still observed that, if comparing the sedentary groups (with and without the addition of sucrose in the diet), we have a lesser concentration of HDL for the animals with the addition of sucrose on the diet. This can also be seen in the trained groups, where the animals with diet supplemented of sucrose had shown a lesser level of HDL in comparison to the animals that had been without receiving sucrose. The sedentary groups presented very superior averages of LDL to those presented by the trained groups, showing that the physical exercise imposed significant reductions in this kind of cholesterol. We conclude that the increase of consumption of simple carbohydrate in the diet increased significantly the levels of total cholesterol, triglycerides, and LDL in sedentary rats. The long-duration physical exercise and moderate intensity determined positive modification in the lipidic profile with reduction of the levels of LDL, increase in the levels of HDL, and decrease in the levels of triglycerides in the trained rats.
Keywords: Physical exercise; lipidic profile and simple carbohydrate